1985
DOI: 10.1037/h0089667
|View full text |Cite
|
Sign up to set email alerts
|

Partial success in behavioral couples treatment of chronic smoking: A case report.

Abstract: The smoking behavior of an oncology nurse with a long-standing history of smoking was reduced with minimal intervention in a context incorporating the smoker's nonsmoking partner. A prototype support program to parallel the smoker's treatment regimen was developed in which the supportive nonsmoking partner monitored subjective feelings, helped develop a hierarchy of smoking locations, created a viable quitting situation, gave verbal encouragement to the smoker, and assisted in relapse prevention. The smoker's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The inclusion issue discussed above suggests that family interventions in smoking cessation avoid encouraging the family to invade the autonomy of the smoker by trying to coerce him or her to quit. A recent case report on a behavioral, couples treatment for chronic smoking illustrates this point (5). The smoker's fiancé was assigned to monitor her smoking behavior, prompt her in her efforts to quit, and give her rewards and encouragement in her efforts to stay quit.…”
Section: Implications For Smoking Cessation Interventionmentioning
confidence: 99%
“…The inclusion issue discussed above suggests that family interventions in smoking cessation avoid encouraging the family to invade the autonomy of the smoker by trying to coerce him or her to quit. A recent case report on a behavioral, couples treatment for chronic smoking illustrates this point (5). The smoker's fiancé was assigned to monitor her smoking behavior, prompt her in her efforts to quit, and give her rewards and encouragement in her efforts to stay quit.…”
Section: Implications For Smoking Cessation Interventionmentioning
confidence: 99%
“…A smoker’s family of origin often has similar smoking behavior to his or her own behavior; thus, if the parents smoke, their children are likely to smoke (7). Several studies found that the spouse’s smoking behavior and support were significantly associated with long-term success in the cessation of smoking (9, 14, 24).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the third session, we continued to conceptualize that the majority of the couple’s marital conflict was centered on their failure to renegotiate their marital relationship following Mr. A’s retirement (27). Therefore, the team prescribed a “courting” ritual to introduce some clarity into the confusion over roles and relationship time (9). The couple was asked to date once a week.…”
Section: The Studymentioning
confidence: 99%
“…Various definitions of social support and types of interventions have made the current literature difficult to interpret. Interventions have included group support (6), telephone contact between group participants (8), involving significant others in all or part of the program (9, 10, 13, 14), relapse programs focused exclusively on social support (1), and clinical interventions with individual couples (7). Some intervention studies have found significant differences (17).…”
mentioning
confidence: 99%